PENYERANGAN RUSIA TERHADAP UKRAINA DITINJAU DARI HUKUM INTERNASIONAL - Diana Octavia Situmeang; Maria Maya Lestari; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Sending Russian military troops into a sovereign state territory to carry out occupationsand special military operations according to international law is a form of violation of statesovereignty or what is known as an invasion. This is an act that violates international peaceand is rejected by the international community because it gives many bad influences to theinternational legal order which influence one another. Besides that, the act of attacking thesovereignty of other countries is also contrary to the theory of sovereignty to internationalcustoms.The type of research used by the author is normative legal research or what is knownas